The pepper trail : history & recipes from around the world - Andrews, Jean, 1923- (University of North Texas Press, 1999)
This is not your everyday cookbook. It is a cultural history of a food--with recipes--put together by an inquisitive scholar, gardener, cook, traveler, and artist who fell in love with peppers more than twenty years ago. During that time I attempted to learn what they are, where they came from, where they moved, and how they affected the cooking in the places they went. I thought others might be interested in what I discovered. It is written in two parts--the history, geography, and background in the first and the cookery in the second, with a bibliography for those who want more. It bombards the reader with an awesome amount of data pieced together from various fragments of information into an overwhelming historical, and geographical study of the pepper pod. It won't hurt my feelings if you just skip to the recipes, but you'll miss a hot story.